Pembuatan Tepung Waluh - Muhanniah Muhanniah; Andi Asni; Arinil Haq (JASATHP: Jurnal Sains dan Teknologi Hasil Pertanian, 2022)
The purpose of this research is the manufacture of pumpkin flour. Waluh flour is a fine grain, yellowish white in color, has a characteristic pumpkin smell, the physical condition of pumpkin flour is strongly influenced by the conditions of the basic ingredients and the drying temperature used. The production of dried pumpkin flour to a moisture content of ± 13% has a fine grain texture, passes a 60 mesh sieve, is yellowish white in color, has a characteristic yellow pumpkin smell. The three drying treatments got the best drying, namely the sun drying treatment which produced a color close to SNI, namely yellowish white, organoleptic parameters obtained the same results.